Implementación de una evaluación formativa mediado por un proceso de trabajo cooperativo en un aula de ciencias sociales del grado octavo (2017)
Searching for answers of how our evaluative process can be transformed into the classroom, we found that the sum of our interests allowed us to form a community of practice in which participation, negotiation and reification (Wenger, 2001) were a constant in the entire investigative process. In the development of this exercise, we can understand that there are several factors that can help to establish a formative evaluation, which is not only reflected in the regulations and official documents of the institution in which we work, but to be put into practice. In this sense, it was possible to reflect on different proposals like Mc. Millan (2007), which allowed us to develop an intervention process where we learned that it is not only purely cognitive work, but that training and learning begin with interactions in society (Johnson and Johnson, 1999). In this way, through Critical Research (Skosmove and Borba, 2004)...